Cross-curricular teaching - Kukovec, Melita (ELOPE (Ljubljana), 2014)
The knowledge learners acquire at school has to be applicable in practice to ensure their motivation for learning. Both cross-curricular and interdisciplinary teaching provide a meaningful way in which students can use the knowledge acquired in one context as the basis for learning in other contexts in and out of school. By using interdisciplinary teaching, the instructor can present the topics in a holistic manner: this approach therefore allows us to activate more of the learners' senses and intelligences. Since Mathematics is one of the least liked subjects by our students, and English one of the favorite ones, the article will demonstrate how we can integrate activities addressing all types of intelligences in a language learning class to achieve the whole range of Bloom's levels of educational objectives on the basis of a novel which includes a wealth of references to mathematics: The Curious Incident of the Dog in the Night-Time by Mark Haddon, which has recently been compulsory reading in all Slovene grammar school programs.
Keywords: Haddon, Mark: The curious incident of the dog in the night-time; inteligentnosti; interdisciplinarni pouk; izobraževalni cilji; književnost; literature; matematični problemi; medpredmetni pouk; motivacija; motivation